Analisis Persepsi Auditor Mengenai Kebutuhan Jasa Audit E-commerce Bedasarkan Perkembangan Bisnis, Sistem Informasi Akuntansi Berbasis Teknologi Dan Keahlian Auditor - I Gusti Ayu Purnamawati; Ni Komang Wiprahasti (Universitas Pendidikan Ganesha, 2022)
Abstract This study aims to determine the effect of e-commerce business development, technology-based accounting information systems and auditor expertise on the needs of e-commerce audit services. This type of research is a quantitative study whose data source comes from primary data in the form of distributing questionnaires directly to respondents. The population in this study are all public accounting firms (KAP) that have obtained permission from the Minister of Finance in Bali Province. The sample selected in this study was using purposive sampling so as to get a total of 59 samples. Data analysis techniques consist of: descriptive analysis, data quality test, classical assumption test, and hypothesis testing with the help of SPSS version 26.0 for windows. The results of this study indicate that the development of e-commerce business has a positive and significant effect on the need for e-commerce audit services, technology-based accounting information systems have a positive and significant effect on the needs of e-commerce audit services and auditor expertise has a positive and significant effect on the needs of e-commerce audit services. . Keywords : E-commerce Business Development, Technology-Based Accounting Information System, Auditor Expertise and E-commerce Audit Service Needs.